2012
DOI: 10.3846/16111699.2011.631742
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study to Diagnose the Outcomes of Customers’ Experiences in Trendy Coffee Shops

Abstract: The purpose of this study is to analyse the influence of experiential marketing on young customers’ experiential values and respectively on their satisfaction and word of mouth and revisit intentions. An instrument was developed to measure how the strategic experiential module (Schmitt 1999) and service quality perceptions of customers influence their experiential values. Data were gathered through questionnaires conducted with 450 respondents to diagnose young customers’ experiences in Gloria Jean's Coffees s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 91 publications
9
70
3
3
Order By: Relevance
“…(2009: 53) tarafından "öznel, içsel tüketici tepkileri (duyular, duygular ve kavrama) ile markanın tasarımı, kimliği, ambalajı, iletişimi ve çevresine ait marka uyarıcılarıyla çağrışım yapan tüketicilerin davranışsal tepkileri" olarak tanımlanmıştır. Schmitt (1999: 60) Marka deneyimi üzerine yapılan çalışmaların çoğu marka deneyimi, müşteri sadakati, ve müşteri memnuniyeti arasındaki ilişkiyi marka deneyiminin stratejik modülleri aracılığı ile analiz ettiğinden bu modüllere deneyimsel pazarlama alanında büyük bir önem verilmektedir (Brakus vd., 2009;Chang ve Chieng, 2006;Nadiri ve Günay, 2013;Zarantonello ve Schmitt, 2010).…”
Section: Marka Deneyimiunclassified
See 1 more Smart Citation
“…(2009: 53) tarafından "öznel, içsel tüketici tepkileri (duyular, duygular ve kavrama) ile markanın tasarımı, kimliği, ambalajı, iletişimi ve çevresine ait marka uyarıcılarıyla çağrışım yapan tüketicilerin davranışsal tepkileri" olarak tanımlanmıştır. Schmitt (1999: 60) Marka deneyimi üzerine yapılan çalışmaların çoğu marka deneyimi, müşteri sadakati, ve müşteri memnuniyeti arasındaki ilişkiyi marka deneyiminin stratejik modülleri aracılığı ile analiz ettiğinden bu modüllere deneyimsel pazarlama alanında büyük bir önem verilmektedir (Brakus vd., 2009;Chang ve Chieng, 2006;Nadiri ve Günay, 2013;Zarantonello ve Schmitt, 2010).…”
Section: Marka Deneyimiunclassified
“…Daha sonra, marka deneyimi kavramı literatüre kazandırılarak, bu yeni alan güçlendirilmiştir (Schmitt, 1999). Marka deneyiminin müşteri memnuniyeti yaratma ve sonrasında müşteri sadakatine dönüştürmede önemli bir rol oynadığı yapılan akademik çalışmalarla kanıtlanmıştır (Brakus vd., 2009;Chang ve Chieng, 2006;Nadiri ve Günay, 2013;Zarantonello ve Schmitt, 2010).…”
Section: Introductionunclassified
“…From the service industry perspective, receiving more attention (quality of service) increases customers' satisfaction, subsequently strengthening bonds (loyalty) between them and a company (Nadiri, Gunay 2013), which may lead to them recommending that company to others (Wu, Liang 2009), which ultimately will reflect on profitability. Service quality has also been regarded as a true reflection of the manufacturing/production success of any business, as investing more resources and efforts towards increasing the quality of a product yields increased annual income (Fajgelbaum et al 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In today's hospitality age, providing satisfactory experiences is seen as important to endure competitive in markets where global competition and modern technology have turned products and services into commodities (Nadiri & Gunay, 2013). The authors indicated that the essential concept of marketing is the conception of customer value for competitive benefit.…”
Section: Customer Experiencementioning
confidence: 99%
“…The strong competition in the business market has led companies to not merely focus on the transformation of economic values from services and products, but also to stage experiences (Nadiri & Gunay, 2013). According to Pine and Gilmore (1998) as cited in Nadiri and Gunay (2013), "an experience occurs when an organization deliberately uses services as the stage, and goods as props, to involve individual customers in a way that creates a memorable event".…”
Section: Customer Experiencementioning
confidence: 99%